2020
DOI: 10.3390/life10120349
|View full text |Cite
|
Sign up to set email alerts
|

Loganic Acid, an Iridoid Glycoside Extracted from Cornus mas L. Fruits, Reduces of Carbonyl/Oxidative Stress Biomarkers in Plasma and Restores Antioxidant Balance in Leukocytes of Rats with Streptozotocin-Induced Diabetes Mellitus

Abstract: The various complications related to diabetes are due to the alteration in plasma components and functional activity of blood cells, hence the search for preventive remedies that would ameliorate the clinical condition of patients is a relevant problem today. The main aim of the present study was to examine the antidiabetic potency and antioxidant effects of loganic acid (LA) in blood of diabetic rats. LA showed a restoration of balance between functioning of antioxidant defense system and oxidative stress in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…The results of current study showed that morin at the dose range of 30–50 mg/kg body weight showed significant improvement in glucose level, lipid profiles (TC, TGs, LDL, and HDL), liver functions (ALP, SGPT, SGOT, and serum creatinine), and body weight in the serum of animals treated with streptozotocin. Reported literatures such as Lo et al [ 42 ] and Dzydzan et al [ 43 ] revealed that treatment with STZ causes an imbalance between plasma oxidant and antioxidant content causes oxidative stress and accelerates the progression of T2DM and its related complications. Hyperglycemia caused due to T2DM also linked with the generation of oxygen free radicals that leads to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The results of current study showed that morin at the dose range of 30–50 mg/kg body weight showed significant improvement in glucose level, lipid profiles (TC, TGs, LDL, and HDL), liver functions (ALP, SGPT, SGOT, and serum creatinine), and body weight in the serum of animals treated with streptozotocin. Reported literatures such as Lo et al [ 42 ] and Dzydzan et al [ 43 ] revealed that treatment with STZ causes an imbalance between plasma oxidant and antioxidant content causes oxidative stress and accelerates the progression of T2DM and its related complications. Hyperglycemia caused due to T2DM also linked with the generation of oxygen free radicals that leads to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced oxidation protein product (AOPP), formed mainly by chlorinated oxidants resulting from myeloperoxidase activity, is produced under oxidative conditions and recognized as a novel marker of oxidative damage [ 8 ]. Not only are AOPPs products of chronic oxidative stress but also they could trigger oxidative stress and further stimulate ROS generation, leading to an unstoppable positive-feedback loop [ 9 ]. AOPPs activate the intrarenal renin-angiotensin system (RAS) through mechanisms involving CD36, protein kinase C alpha, Nox, and nuclear factor- κ B signaling, leading to intrinsic renal cells, including endothelial cells, podocytes, and tubular epithelial cells, and excessive production of intracellular superoxide upon stimulation [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, yellow fruit extract did not contain anthocyanins, but contained 10% more iridoids and only 2% more phenolic acids. Since the main iridoid glycoside of yellow and red fruits of Cornelian cherry is loganic acid, it was also extracted as a separate fraction from the yellow fruits [ 27 ]. The obtained fraction was analyzed and it was revealed that the content of loganic acid was 98% ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It can be assumed that the effectiveness of the extracts in reducing the degree of postprandial hyperglycemia depends on the amount of complex carbohydrates in the diet. However, unlike acarbose (an α-glucosidase inhibitor), extracts of red and yellow fruits of Cornelian cherry may be absorbed into the blood and act not only in the intestine, but show antidiabetic and antioxidant effects in the whole body [ 7 , 27 ].…”
Section: Resultsmentioning
confidence: 99%